Heavy Metals Assessment In Water, Sediments And Selected Aquatic Organisms In Lake Asejire, Nigeria - A., Jenyo-Oni; A. H., Oladele (European Scientific Journal, ESJ, 2016)
Rapid urbanization and industrialization in developing countries have been associated with production and deposition of hazardous wastes in aquatic environments. Heavy metals are major components of these wastes which have been implicated in several metal-related diseases and food poisoning in man. This study evaluated iron, lead, cobalt, nickel, chromium and cadmium concentrations in water, sediment, Nile Tilapia (Oreochromis niloticus) and African river prawn (Macrobrachium vollenhovenii) samples of Lake Asejire, Oyo State, Nigeria. The concentration of these metals was determined spectrophotometrically in three locations along the course of the lake. Results revealed that only iron and lead were detected in water samples. However, all the metals were found in sediments, Nile Tilapia and African river prawn. Iron had the highest mean concentrations (mg kg-1) of 2.392±0.015, 7.4314±1.184, and 1.6100±0.099 in sediments, fish and prawn respectively. Significant differences was found across each sample type for the metals determined. The detection of these metals in Lake Asejire call for close environmental monitoring and adequate public awareness. This is necessary to discourage further pollution which could lead to high metal concentration and metal poisoning.